Detection of prevalence & characterization of thyroid disorder patients in Dhaka: a survey based study - Allam, Md. Shafiul (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2012.